Altered ureido protein modification profiles in seminal plasma extracellular vesicles of non-normozoospermic men - Roy, Rosa; Lorca, Cristina; Mulet, María; Sánchez Milán, José Antonio; Baratas, Alejandro; de la Casa, Moisés; Espinet, Carme; Serra, Aida; Gallart-Palau, Xavier (Frontiers in Endocrinology, 2023)
Extracellular vesicles (EVs) have been recognized as key players in numerous physiological functions. These vesicles alter their compositions attuned with the health and disease states of the organism. In men, significant changes in the proteomic composition(s) of seminal plasma EVs (sEVs) have already been found related to infertility. In this study we analyze the post-translational configuration of sEVs proteomes from normozoospermic (NZ) men, and non-normozoospermic (non-NZ) men diagnosed with theratozoospermia and/or asthenozoospermia, by unbiased discovery-driven proteomics and advanced bioinformatics, specifically focusing on citrulline (Cit) and homocitrulline (hCit) posttranscriptional residues, both considered product of ureido protein modifications. Significant increase in the proteome-wide cumulative presence of hCit together with downregulation of Cit in specific proteins, related to decisive molecular functions, have been encountered in sEVs of non-NZ subjects. These findings identify novel culprits with higher chance to affect fundamental aspects of the sperm functional quality, and define potential specific diagnostic and prognostic non-invasive markers for men infertility.